Tangible images of real life scenes. (May 2017) - Zhang, Xingzi; Goesele, Michael; Sourin, Alexei
Highlights: A way of haptic interaction with the reconstructed real life scenes is proposed. Original images of the real scenes are augmented with the reconstructed meshes. Smooth interactive haptic rendering of multi-million polygons is supported. The feasibility and usability of the proposed method is evaluated in a user study. Abstract: Haptic technologies allow for adding a new "touching" modality into virtual scenes. 3D reconstruction of a real life scene results, however, often in millions of polygons which cannot be simultaneously visualized and haptically rendered. In this paper, we propose a way of haptic interaction with real life scenes where multiple original images of the real scenes are augmented with reconstructed polygon meshes. We present our solution to the problems of haptic model alignment with the images and interactive haptic rendering of large polygon meshes with reconstruction artifacts. In particular, the presented collision detection algorithm is not restricted by any hypothesis and robust enough to support smooth interaction with millions of polygons. The feasibility and usability of the proposed solution is evaluated in a user study. Graphical abstract: